Magnesium as Immediate Management for Suspected Intraoperative Malignant Hyperthermia Crisis: A Case Report from Indonesia - Farida Soenarto, Ratna; Kusuma Manggala, Sidharta; Montolalu, Gabriela; Listyana, Tia; Kurniawan, Celine (Majalah Anestesia & Critical Care, 2025)
Background: Malignant hyperthermia (MH) is a life-threatening disorder triggered by certain anesthetics and characterized by a hypermetabolic state in skeletal muscles. Magnesium sulfate is gaining recognition as a crucial adjunct in the immediate management of MH, particularly when dantrolene is not readily available. This case report presents a successful use of magnesium during an MH crisis, emphasizing its potential as a life-saving intervention in resource-limited settings. The report adds to the growing evidence supporting magnesium's role in early MH management, especially when there is a delay in dantrolene administration.Case Illustration: A 2-year-old healthy boy underwent Achilles tendon lengthening under general anesthesia. Post-induction, the patient developed signs of increased sympathetic activity, muscle rigidity, and hypercarbia. Due to dantrolene unavailability, 400 mg of magnesium sulfate was administered, which successfully reduced muscle rigidity and stabilized hemodynamics. Dantrolene was later given, further improving the patient's condition. The patient was extubated 28 hours later and fully recovered, highlighting the critical role of magnesium in managing this crisis.Conclusion: Early detection and management of MH are crucial for patient survival. In the absence of dantrolene, MgSO4 serves as an effective alternative for immediate intervention. This experience underlines the importance of having alternative treatment strategies in resource-limited settings and stresses the need for continued education and preparedness for MH crises.